Implementing Inquiry-Based Teaching Methods - Anna J. Warner; Brian E. Myers (EDIS)
AEC395, a 5-page illustrated fact sheet by Anna J. Warner and Brian E. Myers, focuses on the nature of inquiry and provides basic guidelines and strategies for implementing inquiry-based teaching methods. Includes useful resources. Published by the UF Department of Agricultural Education and Communication, September 2008.